2018
DOI: 10.26508/lsa.201800028
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Aβ42 is enriched in small vesicles at the presynaptic side of synapses

Abstract: Super-resolution microscopy reveals that Aβ42 is mainly present at the presynaptic side of the synapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 38 publications
6
46
0
Order By: Relevance
“…Another explanation could be that axonal boutons are upregulated due to dendritic spine instability, but over compensation by the axons results in TB loss. Or, as a recent study has shown, Aβ is enriched only at the pre-and not at the post-synapse (Yu et al, 2018), which may also explain why, in our study, axonal boutons are more affected than dendritic spines. In addition, there could be underlying sex differences in these models of AD, which has not been extensively reported.…”
Section: Discussionsupporting
confidence: 49%
“…Another explanation could be that axonal boutons are upregulated due to dendritic spine instability, but over compensation by the axons results in TB loss. Or, as a recent study has shown, Aβ is enriched only at the pre-and not at the post-synapse (Yu et al, 2018), which may also explain why, in our study, axonal boutons are more affected than dendritic spines. In addition, there could be underlying sex differences in these models of AD, which has not been extensively reported.…”
Section: Discussionsupporting
confidence: 49%
“…The absence of HTT phosphorylation reduced presynaptic levels of APP, restored synapse number 326 and PSD length, and attenuated memory deficits in APPPS1 mice. In contrast, there was no effect of the 327 HTT S421A mutation on amyloid plaques, on different pools of Aβ oligomers, or on extracellular and 328 intracellular Aβ42 levels in brain, although the existence of a pool of vesicular presynaptic Aβ has been 329 recently reported (Yu et al, 2018). These results suggest that HTT dephosphorylation regulates synapse 330 homeostasis by modulating presynaptic APP levels rather than modulating APP-derived Aβ production.…”
Section: Htt Phosphorylation App Presynaptic Levels and Synapse Homementioning
confidence: 89%
“…Several studies [32,34] also provide evidence that MVBs can undergo anterograde axonal transport. A study revealed that Aβ42, a neuronal amyloid β-peptide, was absent from the postsynaptic compartments and was enriched only within MVBs in presynaptic compartments [35]. MVBs residing in synaptic boutons have been shown to be in close contact with the presynaptic membrane [36].…”
Section: Exosomes and Neuronal Communicationmentioning
confidence: 99%